Output and Investment for Exponential Growth in Consumption–an Alternative Formulation: And Derivation of their Technological Upper Limits - Mathur, P. N. (Review of Economic Studies, 1964)
Journal Article Output and Investment for Exponential Growth in Consumption — an alternative Formulation: and Derivation of their Technological Upper Limits Get access P. N. Mathur P. N. Mathur Poona Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 31, Issue 1, January 1964, Pages 73–76, https://doi.org/10.2307/2295938 Published: 01 January 1964